Overexpression of MicroRNA-148b-3p stimulates osteogenesis of human bone marrow-derived mesenchymal stem cells: the role of MicroRNA-148b-3p in osteogenesis - Samaneh Mollazadeh; Bibi Sedigheh Fazly Bazzaz; Vajiheh Neshati; Antoine A. F. de Vries; Hojjat Naderi-Meshkin; Majid Mojarad; Mahdi Mirahmadi; Zeinab Neshati; Mohammad Amin Kerachian (BMC, 2019)
Abstract Background Mesenchymal stem cells (MSCs) are attractive choices in regenerative medicine and can be genetically modified to obtain better results in therapeutics. Bone development and metabolism are controlled by various factors including microRNAs (miRs) interference, which are small non-coding endogenous RNAs. Methods In the current study, the effects of forced miR-148b expression was evaluated on osteogenic activity. Human bone marrow-derived mesenchymal stem cells (BM-MSCs) were transduced with bicistronic lentiviral vector encoding hsa-miR-148b-3p or -5p and the enhanced green fluorescent protein. Fourteen days post-transduction, immunostaining as well as Western blotting were used to analyze osteogenesis. Results Overexpression of miR-148b-3p increased the osteogenic differentiation of human BM-MSCs as demonstrated by anenhancement of mineralized nodular formation and an increase in the levels of osteoblastic differentiation biomarkers, alkaline phosphatase and collagen type I. Conclusions Since lentivirally overexpressed miR-148b-3p increased osteogenic differentiation capability of BM-MSCs, this miR could be applied as a therapeutic modulator to optimize bone function.